Compounds from wild mushrooms with antitumor potential - Ferreira, Isabel C F R; Vaz, Josiana A; Vasconcelos, M Helena; Martins, Anabela (Anti-cancer agents in medicinal chemistry, 2010)
For thousands of years medicine and natural products have been closely linked through the use of traditional medicines and natural poisons. Mushrooms have an established history of use in traditional oriental medicine, where most medicinal mushroom preparations are regarded as a tonic, that is, they have beneficial health effects without known negative side-effects and can be moderately used on a regular basis without harm. Mushrooms comprise a vast and yet largely untapped source of powerful new pharmaceutical products. In particular, and most importantly for modern medicine, they represent an unlimited source of compounds which are modulators of tumour cell growth. Furthermore, they may have potential as functional foods and sources of novel molecules. We will review the compounds with antitumor potential identified so far in mushrooms, including low-molecular-weight (LMW, e.g. quinones, cerebrosides, isoflavones, catechols, amines, triacylglycerols, sesquiterpenes, steroids, organic germanium and selenium) and high-molecular-weight compounds (HMW, e.g. homo and heteroglucans, glycans, glycoproteins, glycopeptides, proteoglycans, proteins and RNA-protein complexes).